IMPLEMENTASI JAMINAN MAKANAN HALAL DI HOTEL SYARI’AH MUHAMMADIYAH A. MUIN SAIDI PADANG PANJANG - Mardalis Mardalis; Wina Asty; Rozi Yuliani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Padang Panjang City is known as a region with a strong religious character, where the majority of the population is Muslim. This condition creates moral and regulatory responsibilities to ensure the availability of halal products, including in the hospitality sector. This study aims to analyze how halal food assurance is implemented at Muhammadiyah A. Muin Saidi Sharia Hotel in Padang Panjang. The research employs a descriptive qualitative approach through field observations, in-depth interviews, and document analysis. The findings indicate that the hotel has provided halal food menus. From an Islamic perspective, the provision of halal food is a religious obligation as stated in Qur'an Surah Al-Baqarah: 168. However, the implementation of halal assurance is not merely understood as an administrative requirement, but as part of an ethical and religious commitment in business management. This practice includes the selection of raw materials, food processing systems, and collaboration with certified halal food suppliers. This study emphasizes that strengthening halal tourism requires synergy between local governments, halal certification institutions, and hospitality industry stakeholders to enhance the competitiveness of Padang Panjang as a halal tourism destination.Keywords: Halal Assurance, Sharia Hotel, Halal Food, Halal Tourism, Religious Commitment